2022
DOI: 10.3389/fneur.2022.861992
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inner Ear Macrophages and Autoimmune/Autoinflammatory Mechanisms in the Pathophysiology of Inner Ear Disease

Abstract: Macrophages play important roles in tissue homeostasis and inflammation. Recent studies have revealed that macrophages are dispersed in the inner ear and may play essential roles in eliciting an immune response. Autoinflammatory diseases comprise a family of immune-mediated diseases, some of which involve sensorineural hearing loss, indicating that similar mechanisms may underlie the pathogenesis of immune-mediated hearing loss. Autoimmune inner ear disease (AIED) is an idiopathic disorder characterized by une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…This deposition caused damage to the capillary endothelium, leading to increased vascular permeability, ultimately resulting in endolymphatic hydrops and disruption of the outer hair cells. This proposed mechanism finds support in histopathologic observations from temporal bone studies in both humans and animals [12]. Another study demonstrated that AIED often involves dysfunctional immune responses in peripheral blood mononuclear cells to cochlear antigens.…”
Section: Pathophysiology Of Inner Ear Diseases In Autoimmune and Auto...mentioning
confidence: 71%
See 1 more Smart Citation
“…This deposition caused damage to the capillary endothelium, leading to increased vascular permeability, ultimately resulting in endolymphatic hydrops and disruption of the outer hair cells. This proposed mechanism finds support in histopathologic observations from temporal bone studies in both humans and animals [12]. Another study demonstrated that AIED often involves dysfunctional immune responses in peripheral blood mononuclear cells to cochlear antigens.…”
Section: Pathophysiology Of Inner Ear Diseases In Autoimmune and Auto...mentioning
confidence: 71%
“…Autoimmune and autoinflammatory diseases can affect the inner ear through various mechanisms, although the precise details for all conditions are not fully determined. Presented below are some of the primary mechanisms involved [12]:…”
Section: Pathophysiology Of Inner Ear Diseases In Autoimmune and Auto...mentioning
confidence: 99%
“…The fractalkine signaling pathway has been researched on its participation in the circulation and recruitment of cochlear macrophages: Cx3cr1 (the receptor for fractalkine)‐positive macrophages are recruited into the spiral ganglion for the survival of spiral ganglion neurons, subsequent to HC death induced by diphtheria toxin (Kaur et al, 2015); on the other hand, Cx3cr1‐positive macrophages migrate into the greater epithelial ridge (GER) in response to apoptosis of GERCs, a required process for the inner sulcus formation during cochlear maturation, but the fractalkine signaling pathway is not indispensable for this maturation process (Borse et al, 2021). These cochlear macrophages are presumably maintained not only by self‐renewal through proliferation but also by supply from HSCs after birth, especially in adulthood, as demonstrated by the bone marrow transplantation system as with other types of tissue‐resident macrophages (Miwa & Okano, 2022; Okano et al, 2008). Notably, these cochlea‐resident macrophages were reported not to be found within the organ of Corti (Hirose et al, 2005; Hough et al, 2022; Okano et al, 2008).…”
Section: Cochlear Scs Are Enabled To Acquire Macrophage Phenotypes Du...mentioning
confidence: 99%
“…BLB disruption secondary to cochlear immune and in ammatory responses is a potential contributor to the pathogenesis of hearing loss, and have been associated not only with middle and inner ear infections, but also with autoimmune disorders, acoustic trauma, ototoxicity, presbycusis, and Meniere's disease, among others (11,(25)(26)(27)(28). Preventing inner ear in ammation is thus a clinical aspiration (29).…”
Section: Introductionmentioning
confidence: 99%